Islam, Wanita dan HAM dalam Perspektif Hukum Islam (Analisis Kasus KDRT di Pengadilan Agama Medan) - Siregar, Rayani Hanum (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2009)
It  is  proper  to  thank  the  god  that  the  law  number 23/2004  on  hardness  abolition  in  household  soon  will  be legislated as a constitution which will provide a protection for women,  their  safety  and  rights,  men  and  children  whom  are being  a  hardness  victim  in  household.  This  law had the same point with the law on human rights to live, to be not tortured, privacy  freedom,  thought  and  conscience  as  written  in  at  law number 39/1999 verse 2.But, the authority that bonds  the law is  needed  to  be  re-questioned,  because  that  a  lot  of  hardness chases  raise  among  the  society  out  of  the  civil  law  authority. There chase to chase rise among the society are which  seems lying  under  the  civil  law  authority.  Practically,  this  law  seems has lost its authority. This state arise an ambiguity about its law properness and the proper law to be applied. There are a lot of household hardness chases which areshould be  the  start  point  for  the  government  and  jurists  to  study furthermore the applying of law number 23/2004, because it is practically  not  used  as  reference  law  in  Islamic  court  which managed the familial, marital and divorce affair. It is urgent to know  that  most  of  household  hardness  is  raised  from  the familial  and  household  matter.A  simple  research  about household  hardness  with  its  relation  with  divorce  affair registered  to  the  Islamic  court  in  Medan  that  the  writer had worked indicated that more than 30% of the registered  chases contain  of  household  hardness.  But  because  of  the  hardness matter is out of Islamic court authority made the authority of the law number 23/2004 is dilemma.